Speech Acts in Announcements of Supermarkets and Hypermarkets in Bangkok during the COVID-19 Outbreak - Nuntana Wongthai (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
This qualitative study aims to investigate speech acts in announcements posted at supermarkets and hypermarkets in Bangkok, Thailand during the COVID-19 outbreak, under the framework of the speech acts theory. The communicative functions and hidden intentions in the language used are also examined. At the data collection stage, the definitions of ‘supermarket’ and ‘hypermarket’ were applied to determine the sources. Then, announcements posted at the entrances to branches of supermarkets and hypermarkets in Bangkok were collected during the period of April 1 - 30, 2020, by taking photographs. The criterion for collecting the announcements was that they had to be information relating to activities stores dealing with the pandemic. The total number of announcements found was 239. After the elimination of those with identical content, 32 announcements were used for the analysis. The findings show four types of speech acts: representatives, directives, expressives, and commissives. Such acts perform the communicative functions of informing customers about sanitary measures, requesting cooperation in following government regulations, expressing feelings toward customers, and showing the determination to operate the business in an ethical manner. The indirect speech acts help reveal the intentions of the stores to create a positive image. The study also reveals characteristics of Thai society in terms of hierarchy and solidarity. The study has implications for knowledge of language use during crises and provides insight into the power of language to communicate things over and above literal meanings.